Use of a mHealth System to Improve Antenatal Care: A Literature Review - Tanberika, Fajar Sari; Sansuwito, Tukimin Bin; Hassan, Hafizah Che (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Antenatal care, often known as ANC, is the foundation of programs assisting reproductive health. It is particularly significant in the field of maternal and child health because it offers services to pregnant women from the time of conception until the delivery of the baby. These services are designed to ensure a safe pregnancy and delivery, hence preventing difficulties. The problem of pregnancy difficulties unquestionably has a bad influence on both the mother and her fetus. As a result, it is the reason for the high maternal mortality rate (MMR) in Indonesia. Some of the complications that contribute to this rate include bleeding, eclampsia, complications during abortion, sepsis, and extended partus. By providing routine prenatal care and examinations to medical professionals, it is possible to save the lives of pregnant women who experience problems. Distance is one of the numerous elements that can function as a barrier, and there are many others. During this digitalization era, technology makes it possible to disseminate information to pregnant women to enhance antenatal care. One example of this is using mobile phones in health services, referred to as m-Health. This is a promising option to improve the health outcomes of both mothers and children. This research was conducted to conduct a literature review to assess the advantages of mobile health in enhancing antenatal care. This literature study technique was selected from January 2019 to January 2024. The study approaches chosen are randomized trials, pseudo-experiments, and cluster randomization, designed to adhere to specific inclusion and exclusion criteria. This study utilizes the PRISMA protocol. A thorough electronic search across many databases yielded 683 articles, with 274 from PubMed and 409 from Google Scholar. After independently obtaining and rigorously filtering publications, 6 studies were included in the review. Final Thoughts Based on the findings of the six chosen publications, a critical analysis was carried out, and the conclusion reached was that MHealth is highly significant and beneficial in pregnancy care.